Remote video auditing with real-time feedback in an academic surgical suite improves safety and efficiency metrics: a cluster randomised study. Issue 12 (11th December 2015) - Overdyk, Frank J; Dowling, Oonagh; Newman, Sheldon; Glatt, David; Chester, Michelle; Armellino, Donna; Cole, Brandon; Landis, Gregg S; Schoenfeld, David; DiCapua, John F
Abstract : Importance: Compliance with the surgical safety checklist during operative procedures has been shown to reduce inhospital mortality and complications but proper execution by the surgical team remains elusive. Objective: We evaluated the impact of remote video auditing with real-time provider feedback on checklist compliance during sign-in, time-out and sign-out and case turnover times. Design, setting: Prospective, cluster randomised study in a 23-operating room (OR) suite. Participants: Surgeons, anaesthesia providers, nurses and support staff. Exposure: ORs were randomised to receive, or not receive, real-time feedback on safety checklist compliance and efficiency metrics via display boards and text messages, followed by a period during which all ORs received feedback. Main outcome(s) and measure(s): Checklist compliance (Pass/Fail) during sign-in, time-out and sign-out demonstrated by (1) use of checklist, (2) team attentiveness, (3) required duration, (4) proper sequence and duration of case turnover times. Results: Sign-in, time-out and sign-out PASS rates increased from 25%, 16% and 32% during baseline phase (n=1886) to 64%, 84% and 68% for feedback ORs versus 40%, 77% and 51% for no-feedback ORs (p<0.004) during the intervention phase (n=2693). Pass rates were 91%, 95% and 84% during the all-feedback phase (n=2001). For scheduled cases (n=1406, 71%), feedback reduced mean turnover times by 14% (41.4 min vs 48.1 min, p<0.004), and the improvement was sustained during the all-feedback period. Feedback had no effect on turnover time for unscheduled cases (n=587, 29%). Conclusions and relevance: Our data indicate that remote video auditing with feedback improves surgical safety checklist compliance for all cases, and turnover time for scheduled cases, but not for unscheduled cases.